2012
DOI: 10.1089/end.2011.0498
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Extracorporeal Ligation of Hernia Defects Using an Epidural Needle and Preperitoneal Hydrodissection

Abstract: Purpose: This article presents the extracorporeal ligation of inguinal hernia defects using an epidural needle and preperitoneal hydrodissection. Patients and Methods: Thirteen children underwent laparoscopic extracorporeal ligation of their hernia defect using an epidural needle and preperitoneal hydrodissection. A 5-mm trocar for an operative laparoscope was placed through an infraumbilical incision, a Veress needle for forceps was inserted halfway between the umbilicus and the anterior superior iliac spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 6 publications
0
22
0
3
Order By: Relevance
“…Our laparoscopic, needle-assisted repair (LNAR) technique is similar to the percutaneous internal ring suturing technique, which has been previously described [17], and similarly, described by Tatekawa in 2010 [18], although we were using this technique almost 2 years prior. An important modification from Patkowski [17] is the use of a long and maneuverable, small bore, Tuohy spinal needle rather than an 18-gage injection needle.…”
Section: Discussionmentioning
confidence: 99%
“…Our laparoscopic, needle-assisted repair (LNAR) technique is similar to the percutaneous internal ring suturing technique, which has been previously described [17], and similarly, described by Tatekawa in 2010 [18], although we were using this technique almost 2 years prior. An important modification from Patkowski [17] is the use of a long and maneuverable, small bore, Tuohy spinal needle rather than an 18-gage injection needle.…”
Section: Discussionmentioning
confidence: 99%
“…But during laparoscopy, it becomes obvious automatically. Some authors suggest that PPVs less than 2 mm may be left alone [6], but other had routinely ligated it to avoid development of metachronous hernia [15]. In our series, contralateral hernias were detected in two cases by laparoscopy and were repaired at the same time.…”
Section: Discussionmentioning
confidence: 63%
“…Lifting the peritoneum with the help of 3-mm Maryland forceps ensures a complete encirclement of the internal ring without skip area. Literature search revealed that a similar method was described by Tatekawa [15] in 2012 by the use of an epidural needle and preperitoneal hydrodissection to separate the vas and vessels. But we believe that vas and vessels can be well preserved by lifting the peritoneum by the 3-mm Maryland forceps.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The hydrodissection technique was used in all cases in the current study, which could help surgeons separate the vas deferens and testicular vessels from the peritoneum [7,11,12]. This made a complete circuit of suturing around the neck of the hernial sac, and this was essential to reduce recurrence of hernias.…”
Section: Discussionmentioning
confidence: 99%